A Theory of School Achievement: A Quantum View - James L. Phelps (Educational Considerations, 2012)
What is reality? In order to make predictions, all concepts in a scientific study and subsequent theory must be accurately represented by mathematical principles, and those concepts and principles must embody reality.
Keywords: school achievement; challenges; explanatory; variables; test; development; potentially; objectives; mathematics